Primary Tuberculosis of the Breast Manifested as Abscess: a Rare Case Report - Samita Gupta; Vikram J Singh; Gaurav Bhatia; Kshitiz Dhuria (Acta Medica Indonesiana)
Primary breast tuberculosis is a rare entity. We are reporting a case of primary breast tuberculosis, which presented as breast abscess. On histopathology, it was diagnosed as breast tuberculosis. Aspiration cytology was not done due breast abscess. Patient was put on anti-tubercular drugs. In follow up, after 3 months patient condition was improved.